The creation of man and woman : interpretations of the biblical narratives in Jewish and Christian traditions - Luttikhuizen, Gerard P. (Themes in biblical narrative, 2000)
This volume deals with the three stories about the creation of man and woman in the Hebrew Bible (Genesis 1:26-27; 2:7; and 2:18-25) and with diverse interpretations of these narratives in Judaism and Christianity, particularly in ancient Jewish and Christian texts.